Penanganan Stunting Oleh DPPKB Kota Mataram Dalam Pendekatan Collaborative Governance - Widia Karisma Ashari; Diah Rizki Adekantari; Kartika Juita; Muhammad Aprian Jaelani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stunting remains a public health challenge in Mataram City. The Population and Family Planning Control Agency (DPPKB) of Mataram City plays a crucial role in stunting prevention efforts, but the results have not been optimal due to a lack of cooperation and synergy among parties. The collaborative governance approach offers a solution by emphasizing the importance of cooperation and synergy among the government, communities, academics, and non-governmental organizations. The DPPKB has implemented this approach through the formation of the City Stunting Forum, involving various relevant stakeholders. The forum serves as a platform for coordination, synchronization, and collaboration in stunting prevention efforts. The implementation has yielded positive results, with a decrease in the prevalence of stunting from 23.6% in 2021 to 20.1% in 2023. This approach has proven effective in enhancing cooperation and synergy in stunting prevention efforts, and these efforts need to be continued to achieve the target of reducing stunting in Mataram City.